Urgensi Penegakan Hukum Dan Penguatan Peran Pengawasan KPPU Di Era Industri Digital - Nur Kholis (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2024)
The advent of the digital age brought great change in many aspects including the field of commerce. Trading activities initially done directly become online. Such activities have taken a toll on the implementation of the joint venture control carried out by the commission of the joint venture supervisory the Indonesia Competition Commission (KPPU). Article 30, 1999 rule number 5 on the ban on monopoly practices and unhealthy business competition. This journal was written in order to, first, analyze the importance of law enforcement in preventing unhealthy business competition in the digital industrial age. Second, to analyze the contribution of the KPPU to monitor the unhealthy business competition in the digital market. The study is conducted with qualitative research methods, with a normative-law approach. And providing the basis for law enforcement, the unsound competition for business is the Law. Number 5 chapter 30 in 1999 on the ban on monopoly practices and unhealthy business rivalries. But at its implementation it is still under maximum, still deselect. Therefore needs to be more intensified. In practice, the contribution of the KPPU is less than optimal, requiring new legitimacy and legality that give more authority or authority to the KPPU to be capable of performing maximum, iron-to-profit surveillance duties and minimizing the fraudulent practices of digital trade in the digital age.